The components and capacities of Persian language in Iranian cultural diplomacy - mahdi zolfaghari; ali gholamali (مجله مطالعات ایرانی, 2022)
Introduction Cultural diplomacy, in the contemporary era, is considered as an important factor in decision making among countries in various fields. Therefore, world countries cannot, as before, merely depend on governmental interactions among governments in the framework of conventional diplomacy. They need in order to increase efficiency, to follow meaningful communication with the public, particularly the educated elite, and in this view, deploy various approaches and methods in this regard (Samiei Isfahani & Fathi Mozafari, 2012, p.146).According to Marshal Maclohan, the process of life in the information and communication era, due to the rapid communication and cultural exchanges, has resulted in the noticeable participation of people, and inevitably more consideration of public diplomacy capacities, and consequently more involvement of nations in the international processes. In this way cultural diplomacy has earned a special new position in the foreign policy trends of governments.This essential task has so much evolved, that in addition to the different dimensions and scientific, cultural grounds, has intensely structurally affected the foreign policies of governments.Among the cultural elements of the country's foreign policies, the language and literature factors, are the most effective and influential players for the realization of other objectives. The reason for the emerging importance of cultural diplomacy is to attain a higher level of possibilities and capabilities as compared to the traditional diplomacy. This task is deployed with full capacity, can help attract public confidence, increase the role of identity making, and establish effective socio-cultural stability.For this reason, the government attempt, in line with the realization of cultural diplomacy, to convey most of the information and cultural efficiency criteria in order to create trust and provide national interests. Methodology The basis of this paper’s methodology is analytical descriptive, a library type which is objective oriented and seeks through surveying the capacities of the country's cultural diplomacy criteria to have access to ways for the utilization of the Persian language capacities vis-a-vis cultural diplomacy to achieve ultimate national interests. In this way the procedures deployed will be used in designing efficient cultural diplomacy’s practical and strategic programs and plans. The article's main question is to seek the components of the Persian language soft power capacities in the cultural diplomacy context.It is attempted, in this line, upon examining the theoretical dimensions of cultural diplomacy, through reasoning based upon studies of library sources, to derive the capacities and components of the Persian language soft power in cultural diplomacy. Therefore, the hypothesis of the article is also composed of the fact that Iran enjoys the essential, necessary capacities of Persian language literature and linguistic for the promotion of cultural diplomacy for the sake of materializing national interest’s objectives and consequently influence other governments approach in this regard. Concerning the role of language in cultural diplomacy, Persian language and Persian literature are the most important recognized criteria. This fact is due to various dimensions of art, such as painting which throughout Iran's cultural development has so much mingled with the content of Persian language and literature, that its essence cannot be known without understanding the Persian language heritage. Discussion The important role of language and cultural diplomacy in the information era, simultaneous with the political-cultural domination of the bipolar world order, and its replacement with the soft power instead of hard power, enjoys a special status and position. The writer of this article through the concepts of Persian language and cultural diplomacy studies the cultural interaction in this respect with other nations. As mentioned earlier, language and literature play a key role in cultural diplomacy and are influential for the relations of objectives and national interests of other countries. Due to such facts, in the contemporary world, cultural diplomacy with the objective of influencing the public opinion and consequently affecting the implementation of foreign policy goals, receives more focus than mere conventional diplomacy.In this way the main goal of cultural diplomacy is to impress the general public opinion of nations, organizations and NGOS, through cultural exchanges and offering a positive impression of the countries’ intentions. Based on this reason, ignoring this fact can cause weakness in the country's foreign policies and, as a result, with respect to their relevant position in the international arena.This article; moreover, intends to explain the components and capacities of the Persian language in the soft power of Iran cultural diplomacy. Regarding the Islamic republic of Iran, although foreign policy is intermingled with ideology and geopolitical issues, but relying on the promotion of Iran's international status through the composition and recognition of the cultural diplomacy, observing historical, social and Persian language heritage, can undoubtedly influence the realization of Iran's soft power abilities.Iran, considering its civilization, historical, literature, cultural and religious background enjoys adequate soft power resources that if reaching planned for fruitful objectives and utilizing potential resources can become one of the successful countries in the application of cultural diplomacy in the region and the world (Dadandish & Ahadi, 2011, p.146).The effects of the Persian language over cultural diplomacy is a reality derived from the Iranian history which can be considered as the greatest Persian language capacity for transferring the cultural, civilization values of Iran to other nations. The Islamic Republic of Iran has been able to introduce such concepts to the world within relevant socio-cultural and political context by conveying new concepts in cultural diplomacy which in addition to its Iranian values has Islamic identity. The components exhibit both rich Islamic cultural teaching as well as genuine Iranian cultural values, because the cultural language and literature is an effective media that can be instrumental in strengthening cultural interaction among countries. Conclusion With the fading out of the role of war and emergence of the information and communication of global village, more can be written on cultural diplomacy and its side effects.Cultural diplomacy through conveying the governments and nations the capacities of the relevant cultural concepts, and establishing private, intimate interaction among nations, will provide the possibility of making the related policies and programmers seem more attractive to the world public opinion, and have always been paid attention by the governments. It is unwise, at this juncture of time that cultural diplomacy with such privileges in the communication, information era, being the main priority for advancing international objectives, the Islamic republic of Iran be deprived from this benefit and not take it into its services.Not taking advantage of this opportunity will carry irreparable damage and consequences, and in the long run, will influence the realization of Iran's cultural, political and strategies interests.Cultural diplomacy, on one hand, serves as an instrument for realization of international diplomacy, and on the other hand, is a branch of diplomacy that should be paid attention to by the politicians.The privileges of this sort of activity include, relatively low cost, the software positive nature and public admission, as well as, benefits from the expanded ground of interaction and non-political management.Cultural diplomacy is based on soft power resources as a new method of means for the success of governments in foreign policy. Therefore, recognizing the components and capacities of the Islamic republic of Iran, cultural diplomacy and its timely correct deployment is necessary for the success of its foreign policy. The proper and optimum usage of such resources demands planning and following precise instruction.The Persian literature and Persian language are a valuable, unifying and identity making heritage in the history of this land. Despite the existence of various religions and ethnicities, the unifying factor of Iranian identity is the Persian language. This factor has so much infiltrated of the Iranian society that chapter 2 and article 15 of the constitution has expressly indicated on it. The importance and reflection of Persian language at junctures of time was influential in the expansion of socio-political exchanges, and acted to turn it to the language of science and knowledge in its respective geographic area, as well as a means of international exchange in its related time. In the contemporary time also, the admirers of the rich Iranian culture and literature in other parts of the world, are interested in studying this culture in a way that some universities in Europe and America have offered language study opportunities in this field.This essential possibility, combined with using public and cultural diplomacy, can demonstrate the software power aspects based on cultural attraction, and in this way make the utmost usage of such capacity in the neighboring sphere. The geographical proximity in the Central Asian and Caucasus region demonstrate the deep influence of Persian culture and language in Tajikistan and Afghanistan. Due to the expansion of social developments and communication, since the past time up to now, a noticeable part of people in Iraq, Turkey, Uzbekistan and Pakistan use this language, or at least are familiar with it. This is not merely related to the verbal communication, but considering the link between language effects and cultural transfer, as aspects of soft power, then we can firmly point to the ultra-regional influence of Persian culture in the Muslim world and even the European geographical areas.